Community‐led HIV testing services including HIV self‐testing and assisted partner notification services in Vietnam: lessons from a pilot study in a concentrated epidemic setting. (19th July 2019) - Nguyen, Van Thi Thuy; Phan, Huong TT; Kato, Masaya; Nguyen, Quang‐Thong; Le Ai, Kim A; Vo, Son H; Thanh, Duong C; Baggaley, Rachel C; Johnson, Cheryl C
Abstract: Introduction: The HIV epidemic in Vietnam is concentrated in key populations and their partners – people who inject drugs, men who have sex with men, sex workers and partners of people living with HIV. These groups have poor access to and uptake of conventional HIV testing services (HTS). To address this gap, lay provider‐ and self‐testing and assisted partner notification (aPN) were introduced and delivered by the community. We explored the feasibility and effectiveness of implementing aPN as part of community testing services for key populations. Methods: Lay provider testing and self‐testing was started in January 2017, and targeted key populations and their partners. Since July 2017, aPN was introduced. HTS was offered at drop‐in houses or coffee shops in Thai Nguyen and Can Tho provinces. All self‐testing was assisted and observed by peer educators. Both in‐person and social network methods were used to mobilize key populations to test for HIV and offer HTS to partners of people living with HIV. Client‐level data, including demographic information and self‐reported risk behaviour, were collected on site by peer educators. Results: Between January 2017 and May 2018, 3978 persons from key populations were tested through community‐led HTS; 66.7% were first‐time testers. Of the 3978 clients, 3086 received HTS from a lay provider and 892 self‐tested in the presence of a lay provider. Overall, 245 (6.2% of tested clients) had reactive results, 231 (94.3%) were confirmed to be HIV positive; 215/231 (93.1%) initiated antiretroviral therapy (ART). Of 231 adult HIV‐positive clients, 186 (80.5%) were provided voluntary aPN, and 105 of their partners were contacted and received HTS. The ratio of partners who tested for HIV per index client was 0.56. Forty‐four (41.9%) partners of index clients receiving HTS were diagnosed with HIV, 97.7% initiated ART during the study period. No social harm was identified or reported. Conclusions: Including aPN as part of community‐led HTS for key populations and their partners is feasible and effective, particularly for reaching first‐time testers and undiagnosed HIV clients. Scale‐up of aPN within community‐led HTS for key populations is essential for achieving the United Nations 90‐90‐90 targets in Vietnam.